2005
DOI: 10.1097/01.ta.0000151671.35280.8b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiplatelet Agents on Outcomes for Elderly Patients With Traumatic Intracranial Hemorrhage

Abstract: The use of antiplatelet agents with elderly trauma patients significantly increases the risk of mortality when head injury involves intracranial hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 6 publications
4
83
1
1
Order By: Relevance
“…It has been suggested that an increase of 1% -2% of ICH rates can negate the benefits of antithrombotic therapy [11]. It should be noted that while the mortality of our study is disproportionately higher to what has been described in the literature [29] [30], this is the first paper, to our knowledge, that assesses the adverse effects of APAC use on patients presenting with surgically-treated intracranial hemorrhage.…”
Section: Discussioncontrasting
confidence: 38%
“…It has been suggested that an increase of 1% -2% of ICH rates can negate the benefits of antithrombotic therapy [11]. It should be noted that while the mortality of our study is disproportionately higher to what has been described in the literature [29] [30], this is the first paper, to our knowledge, that assesses the adverse effects of APAC use on patients presenting with surgically-treated intracranial hemorrhage.…”
Section: Discussioncontrasting
confidence: 38%
“…However, they did not match comorbid conditions between cases and controls, with 71.1% of cases manifesting three or more conditions, compared with 34.8% in the control. 11 The greater number of comorbid conditions may have had an impact on the increased mortality seen in the cases. In contrast, a study by Spektor et.…”
Section: Aspirinmentioning
confidence: 99%
“…9 More recent papers have documented the increased risk of death with aspirin therapy in patients with radiographic evidence of intracranial injury. 10,11 Mina et. al found a statistically significant mortality rate (47%) in those taking aspirin compared with controls (8%).…”
Section: Aspirinmentioning
confidence: 99%
“…Due to the prevalent use of antiplatelet medications, many trauma patients present with chemical coagulopathy from medications such as aspirin or clopidogrel. This chemical coagulopathy potentiates the already morbid ATC; as a result, the initial resuscitation and management of these patients requires additional assessment and interventions [5][6][7][8] . Previously, we reported our experience with the Platelet Function Assay-100™ (PFA-100, Dade Behring, Deerfield, IL) identifying clopidogrel use in traumatic brain injury (TBI) and stroke patients with a sensitivity and specificity of 48.6% and 74.8%, respectively 9 .…”
Section: Introducti̇onmentioning
confidence: 99%